A survey on the usage of internet banking services by the state & federal civil servants at Maybank Lawas, sales & service centre / Tury Retap - Retap, Tury (2003)
The purpose of this study are to determine the usage of Internet Banking services by the State and Federal Civil servant who are residing in the district of Lawas. In the study we also explore on how the various demographic variables can influence its usage. The findings will serve as important tool to develop new marketing strategies to promote and encourage the usage of Internet Banking services at Maybank Lawas SSC.